Develop micro magnetic tools - Agrawal, Siddharth (Nanyang Technological University, 2021)
Digital microfluidics is the science that allows individual control of droplets on an open surface. In recent years microfluidics has seen a surge in popularity. Concepts such as the “Lab-on-a-chip” technology, which encompasses “condensing” a laboratory into a microdevice, has shown potential in a myriad of fields such as medicine and biology. Magnetic digital microfluidics is a subset of digital microfluidics that makes use of magnetic forces to manipulate droplets. Magnetic digital microfluidics is increasingly becoming an attractive alternative to other digital microfluidic methods because of the several benefits it offers. For instance, its potential to work with little to no power input has given magnetic digital microfluidics an edge in resource-scarce conditions, such as point-of-care diagnostics (POCD). Considering its advantages, the focus of this report has been limited to the use of magnetic digital microfluidics. The main objective of this project is to develop a novel tool that can undertake all manipulations, namely, transportation, merging, mixing and splitting of droplets, without requiring external power input, by utilising the advantages of magnetic digital microfluidics. The project can be divided into three main components: a) Ideation of the concept and designing of the equipment, b) Ratio of the magnetic particles and silicone, and c) Testing the equipment. This report first provides necessary background information about microfluidics through the literature review. The early protoypes developed are discussed next, and the reasons they were not chosen as the final concept are examined. The report then analyses the novel concept that was developed, including the methodology, laboratory resources used and the procedure involved with the concept. The results are discussed to provide an insight into the feasibility of the concept. Finally, to mitigate any limitations, work is proposed for the future.